Biomarkers and the outcomes of ischemic stroke - Huang, Ying; Wang, Zhenzhen; Huang, Zhi-Xin; Liu, Zhenguo (Frontiers in Molecular Neuroscience, 2023)
Biomarkers are measurable substances that could be used as objective indicators for disease diagnosis, responses to treatments, and outcomes predictions. In this review, we summarized the data on a number of important biomarkers including glutamate, S100B, glial fibrillary acidic protein, receptor for advanced glycation end-products, intercellular adhesion molecule-1, von willebrand factor, matrix metalloproteinase-9, interleukin-6, tumor necrosis factor-a, activated protein C, copeptin, neuron-specific enolase, tau protein, gamma aminobutyric acid, blood glucose, endothelial progenitor cells, and circulating CD34-positive cells that could be potentially used to indicate the disease burden and/or predict clinical outcome of ischemic stroke. We examined the relationship between specific biomarkers and disease burden and outcomes and discussed the potential mechanisms underlying the relationship. The clinical significance and implications of these biomarkers were also discussed.